Innovation and Productivity in the Service Sector: The Case of Thailand - Charoenporn, Peera; Choksawatpaisan, Supawat (Thammasat Review of Economic and Social Policy, 2024)
Various literature investigates the determining factor of research and development (R&D) and the impacts of R&D on firms' innovation performance and productivity. However, most available studies focus on manufacturing firms; little is considered about firms in the service sector. The gap is more evident in the case of service firms in developing countries. This study analyzes the data from the Thailand R&D/Innovation Survey 2011–2018 and applies a structural model that describes the link between R&D expenditure, innovation output, and productivity (the CDM model). The study found a link between R&D activities, innovation output, and productivity in the service sector. The results show that firms with higher R&D intensity tend to offer superior innovation performance. Firms' characteristics and behavioral factors, such as size, openness strategy, foreign share, and exporting behavior, increase the propensity to invest in R&D activity. In addition, innovation output has a positive impact on firm productivity. This study highlights the importance of promoting R&D activities and innovation as the basis for improved productivity of service firms in Thailand and highlights some differences in R&D activities and innovations between the service sector and the manufacturing industry.